Sexual Dysfunctions Related to Drugs Used in the Management of Lower Urinary Tract Symptoms Due to Benign Prostatic Hyperplasia: A Narrative Review on α-Blockers and 5-Alpha Reductase Inhibitors - Antonio La Torre; Caterina Palleria; Irene Tamanini; Andrea Scardigli; Tommaso Cai; Manuela Colosimo; Lucia Muraca; Vincenzo Rania; Davida Mirra; Alessandro Casarella; Gianmarco Marcianò; Giovambattista De Sarro; et al. (Uro, 2021)
This is a critical review of the current literature data about sexual dysfunction as a potential side effect related to drugs commonly used for the treatment of Benign Prostatic Hyperplasia and Lower Urinary Tract Symptoms. In this narrative review, we analyzed data from the literature related to the development of sexual dysfunctions during the treatment of BPH or LUTS. Both α-blockers and 5-alpha reductase inhibitors (5-ARIs) can induce erectile dysfunction, ejaculatory disorders and a reduction in sexual desire. The sexual side effect profile of these drugs is different. Among the α-blockers, silodosin appears to have the highest incidence of ejaculatory disorders. Persistent sexual side effects after the discontinuation of finasteride have been recently reported; however, further studies are needed to clarify the true incidence and the significance of this finding. However, most of the published studies are affected by a weak methodology and other important limitations, with only a few RCTs available. Therefore, it is desirable that future studies will include validated tools to assess and diagnose the sexual dysfunction induced by these medications, especially for ejaculation and sexual desire disorders.